Euro area sovereign yield dynamics: the role of order imbalance - Albert J. Menkveld; Yiu Chung Cheung; Frank de Jong (European Central Bank (ECB), 2004)
We study sovereign yield dynamics and order flow in the largest euro-area treasury markets. We exploit unique transaction data to explain daily yield changes in the ten-year government bonds of Italy, France, Belgium, and Germany. We use a state space model to decompose these changes into (i) a “benchmark” yield innovation, (ii) a yield spread common factor innovation, (iii) country-specific innovations, and (iv) (transitory) noise. We relate changes in each of these factors to national order imbalance and find that Italian order imbalance impacts the common factor innovation, French and Belgian order imbalance impact country-specific innovations, and German order imbalance only changes yields temporarily. Order imbalance, however, does not have explanatory power for the most important factor: benchmark yield innovations.
Keywords: G10; G15; G18; 330; euro; Government bond; international; order imbalance